Faktor-Faktor Yang Mempengaruhi Return On Asset Perbankan Di Asia Tenggara - Abdul Malik; Ahmad Firdaus; Entis Haryadi (Universitas Serang Raya, 2022)
This study examines the extent to which the role of the factors influencing the Return on Assets of banks in Southeast Asia for the 2012-2018 period. Therefore researchers limit themselves only to the influence of Capital Adequacy Ratio, Non Performing Loans, Operating Expenses to Operating Income, Loan to Deposit Ratio to Return On Assets in the Banking Subsector in Southeast Asia for the 2012-2018 period. The data used are the financial statements of each sample company published on the website of the stock exchange in Southeast Asia. The sampling method used was purposive sampling with a total sample of 8 companies for 8 years so that a sample of 64 data was obtained. The method of analysis used in this study is the causality method, with classical assumption testing, as well as statistical analysis of multiple linear regression using SPSS version 25. Based on the results of partial hypothesis testing, it can be concluded that: The Capital Adequacy Ratio variable has a significant positive effect on bank profitability. Non-Performing Loan variables have a significant negative effect on bank profitability. The Loan to Deposit Ratio variable has a positive and insignificant effect on bank profitability. Variable Operating Expenses on Operational Income has a significant negative effect on bank profitability. Simultaneously affect the Return On Assets. The results of the test for the coefficient of determination, the value of R2 shows that the Y variable is influenced by all X variables by 59.3%, the remaining 40.7% is influenced by other variables outside this study. For further research, update the data collection period, research variables and research objects